CHARACTERISTIC OF ORAL MEDICINE PATIENT USING TELEDENTISTRY DURING COVID-19 PANDEMIC - Amtha, Rahmi; Gunardi, Indrayadi; Astoeti, Tri Erri; Roeslan, M. Orliando (Odonto : Dental Journal, 2021)
Background: The COVID-19 pandemic has affected health care systems around the world. Dentistry is one of the most closely related to the production of aerosols or droplets. Minimal visits to a dental clinic or hospital are highly recommended except in emergency cases. The government's recommendation is the use of teledentistry to conduct diagnosis, treatment, and monitoring of diseases. The oral medicine field is fully in charge of this activity and until now it has never been studied how the characteristics of oral medicine patients who use teledentistry services including their level of satisfaction. Method: To describe the characteristic including the level of satisfaction of Oral Medicine patients using teledentistry in Dental Hospital Usakti during pandemic COVID-19. An observational cross-sectional study was conducted in the Oral Medicine Clinic in 31 patients who used teledentistry services at the beginning of the COVID-19 pandemic under informed consent. Validated modified questionnaire and sociodemographic data were collected and satisfaction scores were categorized. Results: The validity of the questionnaire showed Cronbach-alpha 0.83 with a reliability of 0.95 and a separation of 4.49. Most of the subject used teledentistry was female (54.83%), 31-60 years old (51.61%), no history of contact with COVID-19 patient, and prior history of teledentistry (100%, 77.41%, respectively). 93.6% of subjects showed a high satisfaction level in using teledentistry services. Conclusion: The characteristic of oral medicine patients using teledentistry described a high satisfaction level, thus the teledentistry method could be a solution in/after the pandemic era.